Cost Analysis of Noninvasive Helmet Ventilation Compared with Use of Noninvasive Face Mask in ARDS - Kwadwo Kyeremanteng; Louis-Philippe Gagnon; Raphaëlle Robidoux; Kednapa Thavorn; Dipayan Chaudhuri; Daniel Kobewka; John P. Kress (Canadian Respiratory Journal)
Intensive care unit (ICU) costs have doubled since 2000, totalling 108 billion dollars per year. Acute respiratory distress syndrome (ARDS) has a prevalence of 10.4% and a 28-day mortality of 34.8%. Noninvasive ventilation (NIV) is used in up to 30% of cases. A recent randomized controlled trial by Patel et al. (2016) showed lower intubation rates and 90-day mortality when comparing helmet to face mask NIV in ARDS. The population in the Patel et al. trial was used for cost analysis in this study. Projections of cost savings showed a decrease in ICU costs by $2527 and hospital costs by $3103 per patient, along with a 43.3% absolute reduction in intubation rates. Sensitivity analysis showed consistent cost reductions. Projected annual cost savings, assuming the current prevalence of ARDS, were $237538 in ICU costs and $291682 in hospital costs. At a national level, using yearly incidence of ARDS cases in American ICUs, this represents $449 million in savings. Helmet NIV, compared to face mask NIV, in nonintubated patients with ARDS, reduces ICU and hospital direct-variable costs along with intubation rates, LOS, and mortality. A large-scale cost-effectiveness analysis is needed to validate the findings.